Olfactory ensheathing cells and neuropathic pain - Liu, Ji-peng; Wang, Jia-ling; Hu, Bai-er; Zou, Fei-long; Wu, Chang-lei; Shen, Jie; Zhang, Wen-jun (Frontiers in Cell and Developmental Biology, 2023)
Damage to the nervous system can lead to functional impairment, including sensory and motor functions. Importantly, neuropathic pain (NPP) can be induced after nerve injury, which seriously affects the quality of life of patients. Therefore, the repair of nerve damage and the treatment of pain are particularly important. However, the current treatment of NPP is very weak, which promotes researchers to find new methods and directions for treatment. Recently, cell transplantation technology has received great attention and has become a hot spot for the treatment of nerve injury and pain. Olfactory ensheathing cells (OECs) are a kind of glial cells with the characteristics of lifelong survival in the nervous system and continuous division and renewal. they also secrete a variety of neurotrophic factors, bridge the fibers at both ends of the injured nerve, change the local injury microenvironment, and promote axon regeneration and other biological functions. Different studies have revealed that the transplantation of OECs can repair damaged nerves and exert analgesic effect. Some progress has been made in the effect of OECs transplantation in inhibiting NPP. Therefore, in this paper, we provided a comprehensive overview of the biology of OECs, described the possible pathogenesis of NPP. Moreover, we discussed on the therapeutic effect of OECs transplantation on central nervous system injury and NPP, and prospected some possible problems of OECs transplantation as pain treatment. to provide some valuable information for the treatment of pain by OECs transplantation in the future.